PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN SWALAYAN ADA SILIWANGI SEMARANG - Ikfi Khayati, 09.05.51.0097; ., Kunartinah (Students Journal of Economic and Management, 2013)
The study entitled Effect Dimension of Quality of Service Supermarket Customer Satisfaction Siliwangi Semarang There is research to investigate and analyze whether the variables of tangible, reliability, responsiveness, assurance and empathy on the quality of services provided by the Supermarket There Siliwangi partially or jointly have an influence on customer satisfaction, the researchers took the title of "THE INFLUENCE DIMENSION OF SERVICE QUALITY CUSTOMER SATISFACTION IS SILIWANGI SUPERMARKETS SEMARANG". The number of samples used in this study were 100 respondents. The sampling technique used is purposive sampling or by selecting the respondents according to the requirements to become a respondent a scale meet by accident is at least have shopped more than three times and age above 18 years.The result is dimension tangible (X1), reliability (X2), responsiveness (X3), assrance (X4), and empathy (X5) and siginfikan positive effect on customer satisfaction (Y). From the results of the regression equation that has the greatest influence on empathy and responsiveness possessed the smallest influence. This study has limitations that the variables used was limited to the dimensions of quality of service, while there are many other factors that can affect a customers satisfaction. Therefore, further research is suggested to consider other variables that have not been found in this study and a wider sampling.Key words: Variable dimension service quality tangible, Reliability, Responsiveness, Assurance, Empathy and Customer Satisfaction